Development of Moodle-Based E-Learning Media in Workshop and Entrepreneurship Learning - Michelle Firsta Karima Sara; Ambiyar; Dedy Irfan; Hasan Maksum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The rapid transition to online learning due to the Covid-19 pandemic presented challenges in ensuring effective student engagement and comprehension, particularly in subjects like Practical Work and Entrepreneurship. The problem identified is the lack of suitable digital tools to support interactive learning in these subjects, which often rely on hands-on experience and active participation. To solve this problem, this study developed and implemented Moodle-based e-learning media to enhance student understanding and engagement in Practical Work and Entrepreneurship education. The research objective was to assess the effectiveness of this e-learning media in improving students' learning outcomes compared to traditional learning methods. This study employed the Research and Development (R&D) method, involving two groups of students: an experimental group that used Moodle-based e-learning media and a control group that did not receive any additional digital learning support. Data were collected over a period of six months, using pretests and posttests, with statistical analysis conducted via Wilcoxon and Mann-Whitney tests. The results of the study showed significant improvements in the experimental group, with both statistical tests yielding significance values (sig) less than 0.05. These findings highlight the positive impact of Moodle-based e-learning media on students' comprehension of Practical Work and Entrepreneurship. In conclusion, the development and implementation of Moodle-based e-learning media proved to be an effective solution for enhancing student engagement and learning outcomes, particularly in the context of distance learning during the pandemic. This approach offers a scalable and flexible solution for improving education in similar contexts.